Small, micro and medium enterprises access to credit in the Eastern Cape, South Africa - Dlova, Mzwanele Roadwell (My University, 2017)
The study is aimed at empirically investigating the dynamic interaction between the demand and supply factors affecting SMME access to credit in the Eastern Cape. The study is also aimed at conducting a comparative evaluation of lending criteria used by development finance institutions (DFIs) and commercial banks in evaluating SMME funding applications. The study is geared towards proposing a funding framework aligned to the characteristics of SMMEs which can be used by both DFIs and commercial banks to assess applications for SMME funding. In order to meet the objectives of the study, a sample of 80 SMMEs from the manufacturing, construction, services, agriculture, automotive, mining, security, merchandising and retail sectors was, through proportionate stratified sampling, selected from the population of all the SMMEs from the eight metropolitan and district municipalities (Nelson Mandela, Buffalo City, Joe Gqabi, Chris Hani, OR Tambo, Cacadu, Alfred Nzo and Amathole) constituting the Eastern Cape Province. Three separate structured open and closed-ended questionnaires were used to collect data from the 80 SMMEs owner/managers, 8 DFIs’ regional/branch managers and 5 major commercial banks branch managers in the province. The design of both questionnaires was underpinned by the credit rationing theoretical framework as well as the 5C’s of credit (capacity, collateral, capital, condition and character). A response rate of 100% was achieved. Content analysis and Relative Importance Index (RII) were used to analyse data. The results of the dynamic interaction between the supply and demand factors affecting SMME access to credit show that generally, there is an alignment between the SMME and the funding institutions survey results. This shows that the lending criteria of funding institutions are transparent. On the other hand, it is evident that there is poor awareness of the funding institutions criteria by SMMEs. SMMEs seem not to know what funding institutions are looking for when they evaluate funding applications. The results also pointed out that the characteristics of SMMEs in the study are representative of those of SMMEs countrywide. SMMEs in the study are characterised by poor/no business plans, lack of financial statements, lack of collateral, tax clearance certificates, poor cash flow, lack of owners’ contribution and lack of previous industry experience. The results also indicate that funding institutions’ lending criteria do not take into account the unique characteristics of SMMEs in the Eastern Cape. The results of the comparative evaluation of the lending criteria of DFIs and commercial banks show that there are no substantive differences between how commercial banks and DFIs evaluate the credit applications made by SMMEs. Both groups of lenders place significance on the business plans, financial statements, cash flows, owners’ contribution, collateral and experience of owner/managers. Moreover, the study also found that there is significant discrepancy between what the lending documentation of DFIs and commercial banks indicates as key requirements and what the survey results indicate. This means that what funding institutions practice is not congruent with what is enshrined in their lending criteria/policy. If we proxy lend in practice with what the key informants indicated as critical variables, the results show that both groups are more stringent in practice in key areas of their lending criteria. The review of the characteristics of SMMEs in South Africa showed that they lack collateral, are low on savings and experience. Furthermore, they have little capacity for writing business plans and cash flow management. The results here indicate that these are the very same areas which the financial institutions place significant importance on. The findings indicate that the lending criteria used by both groups tend to favour large and well established firms which have the required capacities. Based on the above findings, it is evident that in order to address the SMME access to credit constraint, a new framework that can be used by DFIs to lend to SMMEs needs to be developed. The framework must take into account the peculiar nature of SMME characteristics. Without such an approach, the funding gap for SMMEs in SA will continue. In response to the above findings, the study proposes that government must incentivise funding institutions to innovatively provide capacity building and training programmes targeted at improving the skills and expertise of their staff. It is proposed that DFIs should simplify their loan application forms to cater for the historically low literacy levels of SMMEs in the Eastern Cape. In addition, DFIs should adopt a more streamlined loan application process as well as a shared due diligence process. Credit application forms as well as key lending documents should be standardised. DFIs should conduct road shows to take their potential SMME customers through their application form, how they must be completed and the documents to accompany the form. SMMEs must be personally involved in the gathering of the relevant business plan information as well as in the writing up of their business plans. DFIs must organise quarterly workshops aimed at taking their potential clients through their lending criteria. The SEFA Credit Guarantee Scheme must be reviewed. Government must provide support to its venture capital industry by creating a good investment climate. The study proposes that a knowledge portal that will enable the sharing of knowledge and learning among SMMEs in the Eastern Cape be established. DFIs must set up SMME divisions or units to provide specialised credit services to their SMME customers. DFIs should evaluate SMME credit applications based on alternative risk evaluation methodologies such as the psychometric screening developed by the Harvard University’s Entrepreneurial Finance Laboratory. DFIs should explore alternative means of financing that do not require collateral. To increase SMME access to credit, government should establish specialised banks that can exclusively cater for the needs of the SMME sector. Government could consider granting certain incentives to funding institutions that actively promote SMME financing and have achieved a sizeable SMME loan book.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2017.
Keywords: Small business--South Africa--Finance; Business enterprises--South Africa--Finance; Microfinance--South Africa